On Time Expressions in Mycenaean Greek (Annual of the Faculty of Philosophy in Skopje, 2018)
Time expressions in Ancient Greek are versatile regarding their form, since the semanticrole of Time in this language, like in other Indo-European languages is expressedwith several different cases. The use of different cases is related to the conceptualization ofTime. Although, there is no abundance of time expressions in the Mycenaean documents,the words for 'day', 'month', 'year' are attested and it has been observed that, just as in thePost-Mycenaean period, time expressions can be in genitive, dative-locative, accusative. Inaddition, on some of the tablets, when the date is specified with a month name, phrasesthat consist of forms that, cannot be easily explained as forms of the same case are used.The aim of this paper is to discuss and re-evaluate the meaning of the time expressions(consisting of nouns, nominal phrases or adverbs) found on the Linear B tablets, interms of Time conceptualization. Furthermore, the evidence from the Mycenaean period iscompared with relevant forms from the Post-Mycenaean period in order to deepen our understandingof the diachrony of the time expressions in the Greek language.
Keywords: TIME EXPRESSIONS; MYCENAEAN GREEK; SEMANTIC ROLE